Analisis Laju Korosi Baja Galvanis pada Media Air Sungai Kampar, Rokan, dan Siak Menggunakan Metode Weight Loss - Ikhsan, Mukhlis; Pratama, Arya; Simanungkalit, Yahya Rahmadani; Pradana, Muhammad Ryan; Farhan, Muhammad; Castro, Victor Rio; Nasution, Ahmad Kafrawi; Dahlan, Hendery (Fakultas Teknik UMRI, 2026)
Riau Province has three main rivers: the Kampar, Rokan, and Siak Rivers, which play important roles in water transportation and infrastructure development. River water environments can accelerate the corrosion of metallic materials, including galvanized steel. This study aims to analyze and compare the corrosion rates of galvanized steel in the water media of the three rivers using the weight loss method based on the ASTM G31 standard. The experiments were conducted with immersion time variations of 168, 336, 504, and 672 hours. The observed parameters included mass loss, pH changes, and specimen surface morphology. The results showed that the highest corrosion rate occurred in Kampar River water, reaching 55.888 mpy after 672 hours of immersion, while the lowest corrosion rate was found in Rokan River water at 1.0052 mpy after 168 hours. The chemical characteristics of river water significantly affect the corrosion resistance of galvanized steel.